The art of recovery: outcomes from participatory arts activities for people using mental health services - Stickley, Theodore; Wright, Nicola; Slade, Mike (Taylor & Francis, 2018)
Background: There is a growing evidence base for the use of participatory arts for the purposes of health promotion. In recent years, recovery approaches in mental healthcare have become commonplace in English speaking countries amongst others. There are few studies that bring together these two fields of practice.